Localizing Western Desserts Through Mocaf Boterkoek and Red Rice Puff Pastry Fusion Products - St. Hadijah; Riska Veronika; Jumria Beta; Jamila Jamila; Putu Adi Putra Arimbawa (Institut Pariwisata Trisakti, 2026)
This study aims to localize Western dessert products through the integration of Indonesian local flours and fusion gastronomy approaches. Using an experimental product development design, the study developed two localized pastry products: Mocaf Boterkoek and Red Rice Puff Pastry. The research was conducted in two stages: flour substitution trials and fusion product development. The research was conducted in two stages, namely flour substitution trials and fusion product development. The substitution stage identified 50% mocaf flour as the most suitable level for Boterkoek and 25% red rice flour for Puff Pastry in terms of structural and sensory performance. These formulations were then adapted using Indonesian dessert inspirations, resulting in a nastar-inspired Boterkoek and a molen-inspired Puff Pastry. Sensory evaluation involved 25 semi-trained panelists, 3 expert panelists, and 200 consumer panelists using a seven-point hedonic scale. Both products received consistently positive sensory scores, and paired sample t-test results showed no significant differences across all evaluated attributes. The novelty of this study lies in its integration of local flour substitution and fusion gastronomy within a single pastry innovation framework. The findings indicate that local flours can be successfully incorporated into Western dessert products without reducing consumer acceptance. Keywords: fusion pastry, mocaf flour, red rice flour, boterkoek, puff pastry